The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12035-015-9386-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Vascular Endothelial Growth Factor Treatment Suppresses Early Brain Injury After Subarachnoid Hemorrhage in Mice

Abstract: The role of vascular endothelial growth factor (VEGF) in early brain injury (EBI) after subarachnoid hemorrhage (SAH) remains unclear. The aim of this study was to investigate effects of anti-VEGF therapy on EBI after SAH. C57BL/6 male mice underwent sham or filament perforation SAH modeling, and vehicle or two dosages (0.2 and 1 μg) of anti-VEGF antibody were randomly administrated by an intracerebroventricular injection. Neuroscore, brain water content, immunoglobulin G staining, and Western blotting were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…74,75 Consistent with this hypothesis, inhibition of VEGF activity, either through antibodies directed at the molecule itself or one of its receptors (VEGFR2), significantly ameliorates blood-brain barrier disruption and cerebral edema following experimental aSAH. 76 Several other studies exploring blockade of HIF-1, the transcription factor responsible for VEGF production, demonstrate concurrent reductions in both VEGF expression and brain edema. 58,77,78 Given that a number of anti-VEGF directed therapies, such as the monoclonal antibody bevacizumab, are in clinical use, these strategies merit further exploration for the treatment of cerebral edema in aSAH.…”
Section: Molecular Mechanismsmentioning
confidence: 94%
“…74,75 Consistent with this hypothesis, inhibition of VEGF activity, either through antibodies directed at the molecule itself or one of its receptors (VEGFR2), significantly ameliorates blood-brain barrier disruption and cerebral edema following experimental aSAH. 76 Several other studies exploring blockade of HIF-1, the transcription factor responsible for VEGF production, demonstrate concurrent reductions in both VEGF expression and brain edema. 58,77,78 Given that a number of anti-VEGF directed therapies, such as the monoclonal antibody bevacizumab, are in clinical use, these strategies merit further exploration for the treatment of cerebral edema in aSAH.…”
Section: Molecular Mechanismsmentioning
confidence: 94%
“…The structural and functional integrity of endothelial cells is essential for maintaining stable cerebral autoregulation ( Preckel et al, 1996 ; White et al, 2000 ; Ainslie et al, 2007 ; Guo et al, 2016 ). After SAH, both structural and functional integrity were damaged because of factors, such as the high concentration of ROS/RNS and inflammatory responses ( Figure 1 ) ( Kajita et al, 1998 ; Scharbrodt et al, 2009 ; Szatmari et al, 2010 ; Sabri et al, 2011 ; Qin et al, 2012 ; Liu et al, 2016 ; de Azevedo et al, 2017 ; Shekhar et al, 2017 ; Armstead et al, 2018 ). In inflammatory responses, various inflammatory pathways, such as the NF-κB pathway ( Pawlowska et al, 2018 ), NLRP3 pathway ( Li et al, 2016 ; Shao et al, 2016 ), and TLR4 pathway ( Zhang et al, 2016 ), are activated and have negative effects on the arterial endothelium after SAH.…”
Section: Cerebral Autoregulation Dysfunction After Sahmentioning
confidence: 99%
“…Additionally, there are multiple papers indicating a protective effect of ICV administered VEGF in ischemic stroke [97100] suggesting that CP production of VEGF could have protective effects in stroke. However, it should be noted that Liu et al [101] recently found that ICV administration of an anti-VEGF receptor-2 antibody reduced early brain injury in a mouse SAH model.…”
Section: Choroid Plexus As a Responder To Injurymentioning
confidence: 99%